Reactions of 1,4-dianion of methyl 2-thienyl ketone N-ethoxycarbonylhydrazone with derivatives of carboxylic acids, and the synthesis of pyrazolotriazin-7-ones - Turgut, Z; Öcal, N (MAIK NAUKA/INTERPERIODICA, 2002)
1,3,5-trisubstituted pyrazoles were obtained by reaction of carboxylic acids derivatives with 1,4-dianion of methyl 2-thienyl ketone N-ethoxycarbonylhydrazone. The dianion was prepared by treating the hydrazone with butyllithium in THF at -78degreesC. Besides were prepared 4-methyl (or 4-phenyl)-2-(2-thienyl)-6H-pyrazolo [1,5-d][1,2,4]triazin-7-ones from the corresponding 1,3,5-trisubstituted pyrazoles synthesized respectively, with the use of ethyl pyruvate and ethyl phenylglyoxylate.
Keywords: Chemistry